2021
DOI: 10.3389/fsurg.2021.664454
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ligation Combined With Sclerotherapy for Patients With Acute Esophageal Variceal Bleeding in Cirrhosis: A Meta-Analysis

Abstract: Objective: To evaluate the efficacy and safety of endoscopic variceal ligation + endoscopic injection sclerotherapy (EVL+EIS) to control acute variceal bleeding (AVB).Methods: Online databases, including Web of Science, PubMed, the Cochrane Library, Chinese National Knowledge Infrastructure (CNKI), China Biology Medicine (CBM) disc, VIP, and Wanfang, were searched to identify the studies comparing the differences between EVB+EIS and EVB, EIS from the inception of the databases up to December 30, 2020. STATA 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Prior to PSM, our study showed that patients treated with EVL plus EIS had significantly less varicose recurrence and rebleeding than patients treated with EVL alone, whether at 6-, 12-, or 18-month follow-up. Our results agree with Mansour et al and Wang et al (2,10,14,15). Compared with EVL alone, the EVL plus EIS group had a significant advantage in variceal recurrence and rebleeding for the following principal reasons.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior to PSM, our study showed that patients treated with EVL plus EIS had significantly less varicose recurrence and rebleeding than patients treated with EVL alone, whether at 6-, 12-, or 18-month follow-up. Our results agree with Mansour et al and Wang et al (2,10,14,15). Compared with EVL alone, the EVL plus EIS group had a significant advantage in variceal recurrence and rebleeding for the following principal reasons.…”
Section: Discussionsupporting
confidence: 92%
“…The advantages of our procedure are as follows: (1) the transparent cap is still present at the tip of the lens after EVL, which can fix the varicose vein and facilitate sclerotherapy and can also be used for compression if there is leakage; (2) performing EVL followed by EIS can also reduce the risk of bleeding after ligation of the thick varicose vein; (3) performing EVL earlier can reduce the pressure in the varicose vein and create conditions for subsequent sclerotherapy (less sclerosing agent, long sclerosing agent dwell time); and (4) the procedure does not require special skills and equipment. But, at present, there are still controversies about the efficacy and adverse events of EVL plus EIS and EVL alone for esophageal varicose (2,10,14,15). A meta-analysis discovered that EVL is superior to the combination of EVL and EIS in safety, while no significant differences were found in efficacy (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies suggest that the combined therapy reduces varicose vein elimination time, treatment time, rebleeding, and complication rates compared with EVL alone. 39 However, there are also studies that demonstrate no reduction in rebleeding and mortality rates, but an increase in complications, such as esophageal stricture 40 ; therefore, further research is needed.…”
Section: Treatmentmentioning
confidence: 99%